Physicochemical and rheological properties of aqueous Tara gum solutions - Huamaní-Meléndez, V. J. [UNESP]; Mauro, M. A. [UNESP]; Darros-Barbosa, R. [UNESP] (Elsevier, 2021)
Commercial Tara gum from three sources was purified by precipitation with isopropanol and evaluated on the structural, physicochemical and rheological properties. FT–IR and NMR techniques were used to determine the molecule structure and monosaccharide composition of Tara gum. The physicochemical properties were determined by intrinsic viscosity measurement using capillary viscosimetry and the rheological properties were determined by rotational viscosimetry. The monosaccharide composition of Tara gum galactomannans showed strong influence of their origin, with a mannose/galactose (Man/Gal) ratio varying between 1.54 and 1.85. Intrinsic viscosity of Tara gum in aqueous solution was influenced by its origin and temperature, and it was well correlated to the sigmoidal model. Hydrochloric acid was found to influence intrinsic viscosity below pH 2, however, combined with temperature treatment (80 ∘C), this limit was increased to pH 4. The rheological behavior at diluted concentrations resulted in shear thickening fluid, with an exponential increase of the consistency coefficient with concentration. Apparent viscosity of semi-diluted and concentrated Tara gum aqueous solutions were modeled by the Cross equation, where zero shear viscosity was influenced by gum concentration and temperature, with different activation energies.
Keywords: Galactomannans; Intrinsic viscosity; Rheology; Tara gum; Viscoelastic behavior